Body mass index and weight preception of adolescents in selected private and public schools in Metro Manila Philippines - Cua, Sioksoan Chan. (Thesis-(Master of Science in Clinical Medicine (Child Health))--University of the Philippines Manila.)
Background, significance, rationale:The body mass index (BMI) is an objective method to assess adolescent?s growth and health whereas weight perception (WP) is a subjective perceptual component of the body image which influences health behaviors and outcome. It is important to determine the relationship of BMI and WP in adolescents when intervention aimed at this age group has a greater chance of success. Objective: To assess the relationship of BM with WP of adolescents in private and public schools. Subjects: A total of 2022 adolescents (1186 males, 836 females) from selected private and public schools in Metro Manila, Philippines participated in the study. Design and Methods: Cross-Sectional. The study consisted of two parts: (1) questionnaire with items on self-reported height and weight, WP by word description and sketch selection, and (2) anthropometric measurements of the participants. The intraclass correlation, Kappa statistics, and Pearson Chi-square test were used to analyze data. Results: Based on BMI, 68.8% of the participants had healthy weight, 13% were overweight and 8% were obese while 10.2% were underweight. The prevalence of overweight and obesity was about 3-fold and 4-fold higher in adolescent students from private schools than from public schools, respectively. The prevalence of overweight and obesity was about 2 to 3-fold higher in males in males than in females. More females had healthy weight (78% females vs. 62% males). Self-reported BMI had a positive correlation with measured BMI. Distorted WP by word description and sketch selection was observed among adolescents. He correlation of WP with measured BMI was poor by kappa statistics. Obese or overweight adolescents generally perceived their weight as lighter whereas underweight adolescents generally perceived their weight as heavier. Among healthy weight adolescent, the females had a tendency to perceive their weight as heavier whereas males perceived their weight as lighter. Satisfaction showed significant association with both BMI and WP, and also weight preference (Pearson Chi-square text, p<0.05). The dissatisfaction rate was higher among the adolescents with extremes of weight than those with healthy weight; no gender difference was noted. In general, most of the obese or overweight adolescents wished to become thinner and the underweight desired to be heavier. However, inappropriate satisfaction and no desire for change were also noted among adolescents with unhealthy weight. Among healthy weight adolescents, 36% males preferred to be heavier while 37% females wished to be thinner.Conclusions: Male private students are heaviest compared with all other students. BMI and WP are poorly correlated; WP among adolescents with extreme weights is not realistic. Distorted WP leads to inappropriate weight satisfaction and weight preference.
Keywords: Body mass index; Adolescents; Obesity